EVALUASI KURIKULUM PENDIDIKAN AGAMA ISLAM SEKOLAH DAN MADRASAH - Moch Rizal Umam; Tasman Hamami (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
Curriculum development and implementation of the PAI curriculum in schools and madrasas have different problems and solutions. This research aims to reveal the problems and solutions of the curriculum in schools and madrasas. This research belongs to the type of library research or library research. The results of the evaluation obtained are as follows. First, every individual interested in public schools needs to pay more attention to students' attitude aspects to create generations with social and spiritual sensitivities. Second, from the problem of the development of the Madrasah PAI curriculum, the local government must understand more about Islamic religious education that it is the responsibility of the regional government so that later on, Islamic religious education under the auspices of the Ministry of Religion will receive more attention.